Discrete control algorithms for systems with big dead time for control101 MATLAB toolbox - Bars, Ruth; Max, Gyula; Rossiter, J. Anthony; Keviczky, Laszlo (Cybernetics & Informatics (K&I), 2025)
The first course of control is under a critical review. Both the teaching material covered and the teaching methods require new considerations. Introducing interactivity in the education process makes the learning more successful and enjoyable. MATLAB provides an effective environment for learning and applying different disciplines. Control101 is a new MATLAB toolbox under development which provides tools for interactive learning of control disciplines. This paper presents the framework for teaching discrete control algorithms applied for processes containing large dead times.